Locating Accounting Outsourcing Centres in the Countries of Central and Eastern Europe in the Light of Global Conditions – Research Proposal - Świetla, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The aim of this study is to present is to present what makes the location of accounting outsourcing centres successful given the complexity of their operations. For this purpose, a matrix developed by the author will be used (established on the basis of a pilot study realised in 2016) on the relationship between the complexity of processes and the costs generated in connection with their implementation. The study is currently being prepared (including an analysis of outsourcing market investors, decision-making in the proper sampling, and refining the specific research questions) and its planned execution time is 2017/2018. At this stage, basic research questions and hypotheses were formulated, and a preliminary selection of the statistical method permitting assessment of the studied parameters was made. The study’s results are to be made available to the parties concerned as a tool to support decision-making regarding the location of centres of outsourcing of accounting in the countries of Central and Eastern Europe.